PCR-Based Detection of Angiostrongylus cantonensis in Tissue and Mucus Secretions from Molluscan Hosts - Qvarnstrom, Yvonne (American Society for Microbiology, 2007)
Angiostrongylus cantonensis is a common cause of human eosinophilic meningitis. Recent outbreaks of this infection have shown that there is a need to determine the distribution of this nematode in the environment in order to control transmission. A. cantonensis is generally identified morphologically in the molluscan intermediate host by microscopic examination, which can be labor-intensive. The aim of this study was to develop a PCR-based method to detect A. cantonensis directly from molluscan tissue. A total of 34 Parmarion cf. martensi (Simroth) semislugs, 25 of which were naturally infected with A. cantonensis, were used to develop this assay. Tissue pieces (approximately 25 mg) were digested with pepsin-HCl to recover third-stage larvae for morphological identification or were used for DNA extraction. PCR primers were designed to amplify 1,134 bp from the Angiostrongylus 18S rRNA gene, and the amplicons produced were sequenced for identification at the species level. Both microscopy and the PCR-DNA sequencing analysis indicated that the same 25 semislugs were positive for A. cantonensis, showing that the two methods were equally sensitive and specific for this application. However, morphological detection requires access to living mollusks, whereas molecular analysis can also be performed with frozen tissue. The PCR-DNA sequencing method was further evaluated using tissue from Veronicella cubensis (Pfeiffer) slugs and mucus secretions from infected P. martensi. To our knowledge, this is the first use of a PCR-based method to confirm the presence of A. cantonensis in mollusks collected in the environment.